Sosialisasi dan Praktik Senam Hamil di Posyandu Desa Batursari Kecamatan Sirampog Sebagai Upaya Persiapan Persalinan - Himatul Khoeroh; Miranda Risang Ayu; Melisa Melisa; Novita Rifatul Fahra; Soviana Nur Isnaini (PPNI UNIMMAN, 2023)
It is very important to carry out community service in the from of socialization or education, one of which is exercise during pregnency. This activity was carried out at posyandu desa batursari kecamatan sirampog Sub-dristrict in order to increase the knowledge of pregnant women, reduce discomfrom, and pregnency exercess can facilitate the birth process. The is in line with the government’s efforts to make the Maternal Health Program a success in the from of reducing maternal mortality. The aim of this activity is to increase knowledge for pregnant women as an effort to reduce the occurrence of complication during pregnancy, childbirth and the postpartum period thereby reducing maternal mortality. The results obtained in this activity were that there were 21 pregnant women who took part in the socialization about pregnancy exercise at < 22 weeks and > 22 weeks of gestation and were very enthusiastic about listening to the explanation about pregnancy exercise, while pregnant women demonstrated pregnancy exercise as a only 5 probands were aged > 22 weeks. Pregnant women practiced pregnancy exercise movemonts step by step and during the interview the mother felt directly the positive impact of pregnancy exercise movements. Based on the sicialization activities and practice of pregnancy exercise, it was well received by all pregnant women, proven to be very enthusiastic during the socialization unti the question and aanswer discussion took place and showed an enthusiastic attitude during practice.